2016
DOI: 10.1080/17549507.2016.1193898
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive comparison of approaches to paediatric tube weaning across five countries

Abstract: A multi-model tube weaning approach is commonly adopted by many centres worldwide. In many cases, psychological theory and theoretical orientation is fundamental to tube weaning practice. Further investigation regarding the efficacy and effectiveness of weaning interventions is recommended to ensure clinical practice is based on sound evidence. This may present as a challenge given many interventions occur concomitantly and the psychotherapeutic experience is difficult to evaluate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Weaning stays offered in international clinics or specialized units use programs closely related to ours with a multidisciplinary approach ( 14 , 15 ). In a recent systematic review, Sharp et al described eight studies describing inpatient stay, only two having similar multidisciplinary team of caregivers as ours ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Weaning stays offered in international clinics or specialized units use programs closely related to ours with a multidisciplinary approach ( 14 , 15 ). In a recent systematic review, Sharp et al described eight studies describing inpatient stay, only two having similar multidisciplinary team of caregivers as ours ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, when respondents selected which health‐care providers, they would prefer to be involved in weaning children from a feeding tube, psychologists were chosen by 45.7% of staff. Currently, this professional group within CHQ were reported to be involved in the care of children weaning from feeding tubes by only 1.4% of respondents, even though research has shown that tube weaning services with a psychologist have a shorter tube weaning duration than those not involving a psychologist 4 …”
Section: Discussionmentioning
confidence: 99%
“…Successful weaning from tube feeding is also dependent upon the involvement of a multidisciplinary team 4,6,22,23 . This evidence‐based practice appeared to have been adopted amongst survey participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Families of children with these issues suffer great stress and isolation [4,8,12,23]. A variety of tube weaning methods have been described and discussed [13][14][15][16][17][18] in the literature. Because a dearth of specific information about tube weaning in patients with esophageal atresia exists in recent literature, the authors decided to take a closer look at this population.…”
Section: Introductionmentioning
confidence: 99%